Desain Pembangkit Listrik Tenaga Mikrohidro di Air Terjun Kedung Kayang - Dedi Nugroho; Agus Suprajitno; Gunawan Gunawan (Jurnal Rekayasa Elektrika, 2017)
Kedung Kayang waterfall is located on the border of  Magelang and Boyolali regency of Central Java.  The waterfall is 38 meters high, so it has the potential to be used as a micro hydro power plant (MHP). In designing the MHP, it requires some studies including hydrology, civil, mechanical, and electrical. The purpose of this research is to predict the water discharge, determine the potential of hydro power, selection of MHP sites, design of hydro turbine and electric generator. This research uses Penman Modification method to calculate evapotranspiration, Mock method to calculate water discharge, geographical mapping for MHP sites selection and cross-flow turbine design calculation. This paper presents the results of MHP design consist of MHP capacity, selection of MHP sites, penstock design, cross-flow turbine design and electric generator selection.   The  result showed that  dependable water discharge is 0.143 m3 / sec, effective head is 19.5 meters, hydro potential is 27.33 kW, and electric power that can be produced is 18 kW, length and diameter penstock are 81,74 m and 26,77 m, hydro turbine used cross flow type with outer diameter of the runner is 17,17 cm,  inner diameter is 11,45 cm and width is 59,16 cm. MHP site is located in Klakah village,  Selo Sub-district, Boyolali District.